Let $p:E\rightarrow X$ be a covering map.

Let $U$ be a contractible open subset of $X$.

Is $U$ necessarily an evenly covered open subset, i.e. $p^{-1}(U)$ a disjoint union of open subsets of $E$ homeomorphic to $U$?

I know that if $X$ is path connected and locally path connected, then $U$ is an evenly covered open set. This can be shown by lifting the inclusion $U\hookrightarrow X$ to maps $U \hookrightarrow E$.

What if $X$ is just a general topological space, not necessarily locally path connected and path connected?

  • $\begingroup$ Generally, covering spaces only behave well under some local conditions on the space, e.g. locally path connected and semilocally simply connected. For instance, if your space is locally path-connected, being semilocally simply connected is necessary and sufficient for the existence of a universal cover. $\endgroup$ – Joshua Mundinger Nov 17 '18 at 20:17
  • $\begingroup$ @JoshuaMundinger You're completely right, but what you said is somehow off-topic. Under some local conditions, the space does behave well, as I have mentioned in the question. However, I'm looking for a proof or disproof of the statement without those local conditions. ps. I don't think it has something to do with universal cover. $\endgroup$ – Y. Hu Nov 18 '18 at 13:44

The answer is "yes". To see this, let us recall the concept of a pullback. Given a pair of maps $(p : E \to X,f : Y \to X)$, a pullback of $(p,f)$ is given by a pair of maps $(p^* : E^* \to Y,f^*: E^* \to E)$ such that

(1) $fp^* = pf^*$

(2) For any pair of maps $(u : Z \to Y, v : Z \to E)$ such that $fu = pv$ there exists a unique map $w : Y \to E^*$ such that $p^*w = u$ and $f^*w = v$.

This universal property implies that pullbacks are unique up to canonical homeomorphism. Here is an explicit construction: $$E^* = \{ (e,y) \in E \times Y \mid p(e) = f(y) \}, p^*(e,y) = y, f^*(e,y) = e .$$ If $f$ is the inclusion map of a subspace $Y \subset X$, then we may also take $E^* = p^{-1}(Y) \subset E, p^*(e) = p(e), f^*(e) = e$.

It is well-known that pullbacks of covering projections are covering projections. This means that if $p$ is a covering projection, then so is $p^*$. See Pullback of a covering map.

Lemma : Let $p : E \to X$ be a covering projection and $f_0, f_1 : Y \to X$ be homotopic maps. Then the pullback covering projections $p^*_k : E^*_k \to Y$ along $f_k$ are equivalent which means that there exists a homeomorphism $h : E^*_0 \to E^*_1$ such that $p^*_1h = p^*_0$.

Proof. Let $H : Y \times I \to X$ be a homotopy from $f_0$ to $f_1$ and for $k = 0,1$ let $i_k : Y \times \{ k \} \hookrightarrow Y \times I$ denote inclusion. Form the pullback $(p^* : E^* \to Y \times I, H^* : E^* \to E)$ of $(p,H)$ and the pullbacks $(\pi_k : E^*_k \to Y \times \{ k \}, i^*_k : E^*_k \hookrightarrow E^*)$ of $(p^*,i_k)$, where $E^*_k = (p^*)^{-1}(Y \times \{ k \}) $. Then we may assume that $p^*_k = r_k \pi_k : E^*_k \to Y$, where $r_k : Y \times \{ k \} \to Y, r_k(y,k) = y$.

Now the map $i_0 \pi_0 : E^*_0 \to Y \times I$ lifts to $i^*_0 : E^*_0 \to E^*$. Hence the homotopy $$G : E^*_0 \times I \to Y \times I, G(e,t) = (p^*_0(e),t)$$ which satisfies $G_0 = i_0 \pi_0$ lifts to a homotopy $G' : E^*_0 \times I \to E^*$. The map $G'_1 : E^*_0 \to E^*$ has the property $G'_1(E^*_0) \subset (p^*)^{-1}(Y \times \{ 1 \}) = i^*_1(E^*_1)$. Therefore we get a map $h : E^*_0 \to E^*_1$ such that $p^*_1h = p^*_0$. By lifting $G' : E^*_1 \times I \to Y \times I, G'(e,t) = (p^*_1(e),1-t)$ we obtain a map $h' : E^*_1 \to E^*_0$ such that $p^*_0h' = p^*_1$. It is easy to see that $h' h = id$ (this follows from unique path lifting).

Now let $U \subset X$ be open and contractible. This means that the inclusion $i : U \to X$ is homotopic to a constant map $c : U \to X, c(y) = x_0$. Hence the covering projection $p : p^{-1}(U) \to U$ is equivalent to the pullback of $p$ along $c$. But the latter is easily seen to be a trivial covering $U \times F \to U$ (recall $E^* = \{ (e,y) \in E \times U \mid p(e) = c(y) = x_0 \} = \{ (e,y) \in E \times U \mid e \in p^{-1}(x_0)) \} , p^*(e,y) = y$). This means that $U$ is evenly covered.

Note that it suffices to assume that $i : U \to X$ is inessential which is weaker than $U$ contractible.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.